NEUROCOGNITIVE PERFORMANCE AT RETURN TO PLAY IN ELITE YOUTH HOCKEY PLAYERS WITH SPORT-RELATED CONCUSSION. Issue 7 (11th March 2014) - Taylor, K; Brooks, BL; Schneider, KJ; Blake, TA; McKay, CD; Meeuwisse, WH; Barlow, KM; Kang, J; Emery, CA
Abstract : Background: Neurocognitive recovery following sport-related concussion is important for re-injury risk reduction. In elite youth hockey, it is unknown if neurocognitive function returns to baseline values at the time of medical clearance to return to play (RTP). Objective: To determine if ImPACT composite scores have returned to baseline values at the time of medical clearance to RTP. Design: Prospective case series. Setting: Sport Medicine Clinics (Alberta, Canada). Participants: Concussed elite male and female youth (13–17 years) ice hockey players (n=68) and healthy controls (n=22) completed ImPACT and SCAT2 testing at baseline and RTP following concussion. Main outcome measurements: Team therapists/trainers referred concussed players to the study sport medicine physician. The physician determined RTP via symptom resolution and SCAT2 score normalization. Physicians were blinded to ImPACT (Immediate Post-Concussion Assessment and Cognitive Testing) composite scores (verbal memory, visual memory, reaction time and visual motor), which were used to evaluate neurocognitive performance. Results: Comparisons between baseline and RTP ImPACT scores were based on reliable change (RC) scores derived from a sample of healthy players tested twice at baseline within 2 weeks (RC scores with 90% CI: verbal memory +/−14; visual memory, +/−15; reaction time, +/−0.1; and visual motor, +/−8). All four ImPACT composite scores were normalized at RTP in 73.5% (95C% CI: 61.5–82.8) of concussed participants and all but one [95.5%; 95% CI:70.39–99.46) controls. In the concussed players, 25.0% (95% CI: 16.0–36.9) had 1 composite score not return to baseline at RTP. One player had three composite scores not return to baseline at RTP. Conclusions: Elite hockey players are often cleared for RTP without the benefit of knowing neurocognitive performance on ImPACT. In this cohort, 25% of concussed players who were cleared to return to hockey had 1 composite score that had not yet returned to baseline. These results may have implications for tertiary prevention.